Measuring and Improving Employee Engagement (A Study in PT. Svara Inovasi Indonesia) - Oktanofa, Adam Kurnia; Arliawan, Fredo Adrian; Gustomo, Aurik (IPTEK Journal of Proceedings Series, 2020)
For the past 15 years, radio and music industry trend is decreasing. One of the causes is â€œdisruptionâ€ from Radio Internet Pureplay such as Spotify, Joox, etc. Svara came with â€œBeyond Disruptionâ€ concept that can be saved radio and music industry by starting Radio Digital Transformation. Nowadays, the growth of IT Start-Up Company keeps increasing. which also followed by the increased number of skilled IT workers. The turnover rate over the IT Company also increases. Most of the employees stayed for a short period then moved to another company. This high turnover rate causes decrease in productivity that affected the revenue of the company since low level of employee engagement. In this paper, PT Svara Inovasi Indonesia will be studied and improved employee engagement. The factors of employee engagement level are measured through the data collected by questionnaire. The main objective of the study was to measuring and improving the employee engagement level on PT Svara Innovasi Indonesia. To measure employee engagement with suggestive improvements, the study uses 3 models; Gallup Q12, Aon-Hewitt Employee Engagement Driver, and Deloitte Simply Irresistible Organization model. The result is identified that â€œstayâ€ component from employee engagement level is low. This caused by low level of recognition, rewards, and work-life balance. This could be improved to increase engagement level, productivity and reducing turnover.